Big Data and Law: A Practitioner's Guide - Caldarola, Maria Cristina; Schrey, Joachim (Verlag C.H.BECK Recht - Wirtschaft - Steuern, 2021)
Caldarola/Schrey Big Data and Law “Big Data” refers to large amounts of data originating from various sources which are stored, processed and analysed with specific applications to obtain all kind of (inter-) dependency analyses, environmental and trend research, and for system and production control purposes. As in data mining, knowledge discovery is a priority for Big Data applications. Big Data is now seen as a new source and a “reserve” of additional revenue. When dealing with Big Data, it is not enough to have the necessary technical expertise and infrastructure. Rather, the legal scope must also be observed. As a result of the applicability of the EU General Data Protection Regulation since 25 May 2018 and the associated potentially substantial fines for data protection infringements, data protection supervisory authorities in particular will intensify their supervisory measures and also focus their attention on Big Data applications. With numerous guidelines and graphics, this book is a practical legal guide to gathering, storing and analysing personal and other types of data in Big Data applications. It provides comprehensive, practice-oriented assistance and reliability for planning everyday business in a Big Data environment.